Liver Disease and Treatment Needs of Asymptomatic Persons Living With Hepatitis B in Senegal. (28th October 2022) - Ramírez Mena, Adrià; Thioubou, Mame Aissé; Diallo, Kalilou; Tine, Judicaël; Ngom, Ndeye Fatou; Fortes, Louise; Ndiaye, Kiné; Karasi, Jean-Claude; Seguin-Devaux, Carole; Goedertz, Henri; Diouf, Daouda; Seydi, Moussa; et al.
Abstract: The prevalence of active hepatitis B among asymptomatic persons remains unclear in Africa. Of 1206 newly diagnosed persons in Senegal, 12.3% had significant fibrosis and 31.3% had hepatitis B virus (HBV) DNA levels >2000 IU/mL. Overall, 128 (12.9%) were eligible for antiviral therapy. Generalized HBV screening allowed the identification of a large population requiring HBV care.